Measurements using optic and RF waves - Fornel, Frédérique de, 1953-; Favennec, Pierre-Noël (ISTE., 2010)
Scientific and technical knowledge for measurements in modern electromagnetism must be vast as our electromagnetic environment covers all frequencies and wavelengths. These measurements must be applied to fields as varied as nanotechnologies, telecommunications, meteorology, geolocalization, radioastronomy, health, biology, etc. In order to cover the multiple facets of the topic, this book sweeps the entire electromagnetic spectrum, from several hertz to terahertz; considers distances ranging from nanometers to light-years in optics; before extending towards the various measurement techniques.